On R&D and the undersupply of emerging versus mature technologies - Tom-Reiel Heggedal (Statistics Norway, Research Department, 2008)
An important policy question is whether research and development (R&D) in new, emerging technologies should be more subsidized than R&D in other more mature technologies. In this paper I analyze if innovation externalities caused by knowledge spillovers from private firms may warrant a differentiated R&D policy. I find that R&D in emerging and mature technologies should not be subsidized equally. The reason is that R&D in the two technologies is not equally undersupplied in the market due to differences in their knowledge stocks. R&D in the mature technology should be subsidized more when the sum of the output elasticities with respect to labor and knowledge in R&D production is high, while R&D in the emerging technology should be subsidized more when the elasticities are low.
Keywords: O32; O38; 330; Endogenous growth; Innovation policy; Technological spillovers; Sector-specific R&D.